Perancangan Aplikasi SPPD Berbasis Mobile Menggunakan Metode Rapid Application Development (RAD) - Alda, Muhamad; Wardana, Aji; Isnan, Muhammad Hafi Isfahan; Hibrizi, Muhammad Naufal Fathin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Members of the North Sumatra Provincial DPRD Secretariat Council carry out their official travel duties out of town, then it is the duty of honorary employees to make official travel orders. The North Sumatra Provincial DPRD Secretariat also has an information system for arranging official travel. Namely the SIJADIN system, but this system is still Web-based where the author makes innovations so that the system is redesigned using Android. The author created the same information system but with complete features. This information system was designed using Mobile programming. It is hoped that this information system will help North Sumatra Province DPRD Secretariat employees to make official travel orders effectively and efficiently. In the problem above, the author created a system using the Rapid Application Development (RAD) method. This method is used because the application being designed is structured in stages and the development process does not take much time and the results of the software being developed can be known without waiting a long time because the work is carried out in divided into stages, it is hoped that the application design can make employee performance efficient in making SPPD applications.